The Significance of Hand Tool Skills in the Fourth Industrial Revolution: A Focus on the Construction Concept - Mhlongo, Khethukuthula Mayisatshaba; Khoza, Samuel Dumazi; Skosana, Ndlelehle Miskien (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2023)
The study investigated the significance of hand tool skills in the Fourth Industrial Revolution (4IR) era in teaching the construction concept in a civil Technology subject. The construction concept is one of the most practical concepts in civil Technology that is learnt in the Further Education and Training stream in the South African education curriculum. It deals with issues that cut across bricklaying and plumbing among others. Purposive sampling was used to select six teachers to take part in the study. Classroom observation and semi-structured interviews were used as instruments for data collection. The Technological Pedagogical and Content Knowledge framework was used to support the study. Data were analysed descriptively for classroom observations and through verbatim quotes for interviews with teachers. The study's findings discovered that teachers lack knowledge and understanding of 4IR and that they fail to use instructional practices that prepare learners for the 4IR jobs because of a lack of support from school officials. Teachers also lack the essential technologies to prepare learners that would thrive in the 4IR workplaces; hence their instructional practices are still using hand tools in the construction concept, which is not significant to the current trends. The study recommends that the Department of Education needs to train teachers to be ready to prepare learners for the 4IR jobs within the construction sector.